REQUISITOS FUNDAMENTAIS PARA A CRIATIVIDADE EM CONTEXTO ORGANIZACIONAL: UM ESTUDO QUANTITATIVO EXPLORATÓRIO - Brandão Pereira, Rui Filipe; Remondes, Jorge (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2023)
Creativity plays a predominant role in organisations and fosters the spirit of innovation, generating competitiveness and differentiation in the market. The organisational climate and context where employees are located play a fundamental role in creating conditions that induce critical thinking and organisational development. This article reviews the literature on creativity, its application in the organisational context and how important it can be in contributing to organisational growth and development. The overall objective is to confirm what the fundamental requirements for creativity in organisational context are. The methodology followed is of a quantitative nature, having used during the COVID-19 Pandemic the application of an online questionnaire survey and registered 104 corporate boards as respondents. The results obtained allow us to conclude that training is determinant for employees’ creativity, innovation is directly related to the degree of creativity, employees working in teams tend to be more creative and creativity influences business development.